Restorative Justice in Military Justice Practices in Domestic Violence Cases Committed By TNI Soldiers - Verena Jessica Giovani; Tetty Melina Lubis; Hamzah Rokhmat (Universitas Muhammadiyah Palu, 2024)
Not only does the TNI community experience a high rate of domestic violence in Indonesia, but there have also been numerous instances of TNI soldiers engaging in violent domestic relationships. Nearly every TNI soldier who violates domestic abuse laws faces a prison sentence. In actuality, handling domestic abuse crimes can be better accomplished by using restorative justice as an alternative. In line with the goals of Law Number 23 of 2004 for the Elimination of Domestic Violence, this study will address the use of restorative justice to assist attempts to return the situation to its pre-violent state. This study's empirical juridical methodology is bolstered by a case approach derived from the Military Court II 08 Jakarta's ruling. The study's findings show that, from 2016 to 2022, TNI members who commit domestic abuse have never received additional therapy from Military Court II 08 Jakarta. Furthermore, the Panel of Judges has utilized the principle of Restorative Justice in multiple instances of domestic violence committed by TNI soldiers based on legal considerations. It should be noted, however, that there are no guidelines or regulations governing the implementation of Restorative Justice in the military justice system. Thus, in order for Military Court Judges to use Restorative Justice in the Military Court System, it is imperative that SEMA and internal TNI provisions be issued.